Analysis of Determinants of the Speed of Adjustment to Target Capital Structure of Companies in Developing Economies - Nivorozhkin Eugene; Kireu, Eugeniu (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2020)
The financial stability of a company, along with its operational effectiveness, depend on whether the company endeavours to optimise its capital structure, and the speed at which it can do so. The purpose of this article is to assess the relative impact of influential factors on the speed of adjustment to the optimal capital structure of companies in emerging markets. The relevant factors in question include corporate determinants, macroeconomic determinants, the specific financial characteristics of BRICS companies, and other pertinent external macroeconomic conditions. To achieve this, we conducted a comparative study of various assessment methodologies and examined their findings. Within the scope of the overall study aims, we considered various models of assessing the speed of adjustment and identified those study methods most frequently used. We identified the determinants of optimal capital structure and the related speeds of adjustment, and suggested hypotheses based on assumed assessment results. We then proceeded to analyse the sustainability of those results and gauge the overall robustness of our approach. The study results reveal that the speed of adjustment to target capital structure in developing economies is significantly higher than in advanced economies. The results indicate that these speeds vary in the range of 31–46% for book values of financial leverage and 60–79% for its market values. An empirical analysis of these results also showed that companies with a less-than-optimal debt level achieved the optimum level much quicker, and the speed of adjustment thereby depends heavily on the absolute value of the company money flow. Moreover, this is especially true in those companies with an excessive leverage value. Financial instability in the markets, meanwhile, had a positive effect upon the speed of adjustment for Chinese and Brazilian companies, while in the other BRICS countries the change of the speed of adjustment in the period of crisis finds no confirmation.